Strategies and dominants: a hundred years with Josef Švejk - Fořt , Bohumil (Bohemistyka, 2025)
It is obvious that Hašek’s Fateful Adventures of the Good Soldier Švejk during the World War (1921–1923) is centred around its main character – Josef Švejk. This study departs from the traditional interpretive model that mimeticizes Švejk and makes him part of the “Czech myth” and attempts to analyze this character as the central point of the narrative-semiotic build of the entire novel. Therefore, the study defines three principles based on the functions of Švejk as a character and his functions, physical, verbal and semantic, and shows how through these principles is essentially involved in this construction.